Gene expression of MAGE‐A3 and PRAME tumor antigens and EGFR mutational status in Taiwanese non–small cell lung cancer patients. Issue 5 (12th August 2016) - Pan, Szu‐Hua; Su, Kang‐Yi; Spiessens, Bart; Kusuma, Nicole; Delahaye, Nicolas F; Gruselle, Olivier; Myo, Aung; de Creus, An; Louahed, Jamila; Chang, Gee‐Cheng; Yu, Sung‐Liang; Yang, Pan‐Chyr
Abstract: Aim: To determine the frequency of expression of the tumor‐associated antigens (TAAs) melanoma‐associated antigen A3 (MAGE‐A3) and preferentially expressed antigen of melanoma (PRAME) and the rate of EGFR mutations in a Taiwanese non–small cell lung cancer (NSCLC) population including only adenocarcinomas and squamous cell carcinomas. Furthermore, to investigate associations between TAA expression and EGFR mutations and to evaluate these TAAs as prognostic markers for overall survival. The occurrence of single nucleotide polymorphisms in MAGEA3 and PRAME was also assessed. Methods: Archival fresh‐frozen tumor tissue specimens were tested by quantitative reverse transcription polymerase chain reaction assays to detect MAGE‐A3 and PRAME expression. EGFR mutations were detected by mass spectroscopy and single nucleotide polymorphisms by gene sequencing. Results: Of the 156 adenocarcinomas examined, 3.3% expressed MAGE‐A3, 32.2% expressed PRAME and 62.8% had EGFR mutations. Of the 128 squamous cell carcinomas, 29.8% expressed MAGE‐A3, 59.2% expressed PRAME and 20.5% harbored EGFR mutations. TAA expression was similar across subgroups determined by patient or tumor characteristics. There was no association between TAA expression and EGFR mutation status and TAA expression was found not to be a prognostic marker for survival. Single nucleotide polymorphisms were identified, one of which with a possible impact on MAGE‐A3 expression. Conclusions: In this NSCLC population, expression of MAGE‐A3 and PRAME was more frequent in squamous cell carcinomas than in adenocarcinomas tumors. EGFR mutations were not associated with TAA expression for either histology and were three times more frequent in adenocarcinomas than in squamous cell carcinomas tumors.